2016
DOI: 10.1073/pnas.1518501113
|View full text |Cite
|
Sign up to set email alerts
|

Small genome of the fungus Escovopsis weberi , a specialized disease agent of ant agriculture

Abstract: Many microorganisms with specialized lifestyles have reduced genomes. This is best understood in beneficial bacterial symbioses, where partner fidelity facilitates loss of genes necessary for living independently. Specialized microbial pathogens may also exhibit gene loss relative to generalists. Here, we demonstrate that Escovopsis weberi, a fungal parasite of the crops of fungus-growing ants, has a reduced genome in terms of both size and gene content relative to closely related but less specialized fungi. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
79
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 68 publications
13
79
1
Order By: Relevance
“…We also identified several BGCs appearing on DNA with similarity to plasmids, suggesting that Pseudonocardia associated with fungus farming ants may be inclined to pass around BGCs via horizontal gene transfer. Genome sequencing recently revealed that Escovopsis weberi has a reduced genome, most likely due to its role as a parasite on the fungal garden of attine ants (de Man et al, 2016). Despite loss of many genes, however, E. weberi has maintained a number of genes involved in secondary metabolite biosynthesis, suggesting that colony-life in fungus-growing ants are characterized by ongoing evolutionary arms races between microbial symbionts.…”
Section: Discussionmentioning
confidence: 99%
“…We also identified several BGCs appearing on DNA with similarity to plasmids, suggesting that Pseudonocardia associated with fungus farming ants may be inclined to pass around BGCs via horizontal gene transfer. Genome sequencing recently revealed that Escovopsis weberi has a reduced genome, most likely due to its role as a parasite on the fungal garden of attine ants (de Man et al, 2016). Despite loss of many genes, however, E. weberi has maintained a number of genes involved in secondary metabolite biosynthesis, suggesting that colony-life in fungus-growing ants are characterized by ongoing evolutionary arms races between microbial symbionts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, extensive gene loss was found in populations of the cyanobacterium Prochlorococcus highly specialised to narrow ecological niches (Dufresne et al, 2005). In fungi, a reduced genome and gene content was found in Escovopsis weberi, a highly specialised mycoparasite of ant-cultivated fungi, when compared with unspecialised mycoparasitic species in the closely related genus Trichoderma (De Man et al, 2016), suggesting that gene loss in E. weberi is connected to its narrow niche and highly specialised lifestyle. Gene loss is very well documented for microbes that specialised as obligate biotrophs, with extremely reduced genomes being reported for bacteria living in association with different eukaryotes (McCutcheon & Moran, 2012).…”
Section: Specialised Vs Unspecialised Mycorrhizal Fungi?mentioning
confidence: 99%
“…E. weberi degrades the hyphae of L. gongylophorus before direct physical interaction, suggesting that the pathogen secretes toxins and/or enzymes that can break down host mycelium before contact occurs . The recently sequenced E. weberi genome encodes for a variety of secondary metabolite biosynthesis gene clusters . Some of these gene clusters including polyketide synthase gene clusters were significantly up‐regulated when growing with L. gongylophorus .…”
Section: Introductionmentioning
confidence: 99%
“…The recently sequenced E. weberi genome encodes for a variety of secondary metabolite biosynthesis gene clusters . Some of these gene clusters including polyketide synthase gene clusters were significantly up‐regulated when growing with L. gongylophorus . Moreover, crude extracts of several Escovopsis species were reported to inhibit the growth of L. gongylophorus .…”
Section: Introductionmentioning
confidence: 99%